Hakikat Penelitian Pendidikan dan Relevansinya Terhadap Berpikir Terbuka, Kritis, Inovatif dalam Mempersiapkan Karya Ilmiah di Era Society 5.0 - Fauziah Gafur; Syukrina Kamilah; Salsabila Amanda Fauziah; Rully Hidayatullah; Harmonedi Harmonedi (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
The Society 5.0 era demands advancements in educational research to generate innovation and scientifically based solutions. However, the low quality of research is often caused by a lack of open, critical, and innovative thinking. Open-mindedness allows researchers to embrace new perspectives, critical thinking helps analyze issues in depth, and innovative thinking fosters the emergence of fresh ideas relevant to current developments. This study aims to examine the nature of educational research and its role in strengthening thinking skills to enhance the quality of scientific work. Using the library research method, this study analyzes the concepts, methodologies, and relevance of educational research in the digital era. The findings indicate that open, critical, and innovative thinking in research can improve the quality of education and support adaptation to global changes. Additionally, high-quality research serves as a foundation for more effective education policies. Strengthening thinking skills in educational research is essential to producing higher-quality scientific works that are relevant to the development of Society 5.0.